Micro-indented-mechanically-engineered Ni-Fe-Mo-Cu alloying electrocatalyst for oxygen evolution reaction: A cost-effective approach for green hydrogen production. (20th December 2021) - Khan, M. Faizan; Qurashi, Ahsanulhaq
Abstract: Hydrogen is the next-generation clean and ecofriendly alternative energy source. Its generation through water splitting is promising for sustainable production. The advancement of highly effective, stable, and profitable materials are the key challenges in catalyst design. In this direction, a novel single-step fabrication strategy employing micro-indented-mechanically-engineered (MIME) multinary (Ni-Fe-Mo-Cu) bare metallic material is an intriguing attempt to develop a highly efficient electrocatalytic oxygen evolution reaction (OER) at lower overpotential. This novel idea is based on applying compressive load through a rolling mill to generate micro-indents that act as active sites for the hydroxyl ions for accelerating OER. The Linear sweep voltammetry (LSV) curves showed 10 mA cm −2 could be generated employing the MIME electrode of 1000 N load at a lower overpotential. Electrochemical Impedance Spectroscopy (EIS) revealed that the lowest polarization resistance (Rp ) was obtained at the same load. The electrocatalytic activity of the electrode was sustained by the formation of the porous oxide film which eventually improved the overall electrochemical surface-area of the electroactive film composed of respective alloying elements confirmed by comprehensive X-ray photoelectron spectroscopy (XPS) analysis. Graphical abstract: Image, graphical abstract